Efficiency gains and time-savings of permanent panels in the WTO dispute settlement - Louise Johannesson (Research Institute of Industrial Economics (IFN), 2018)
The dispute settlement mechanism (DSM) is today the most active dispute resolution forum in the world. However, its success has also led to increased processing time of disputes, which, in turn, increases the cost of using the World Trade Organization (WTO) as a way to resolve trade conflicts. I investigate whether the DSM can be improved by introducing a permanent panel of judges, to replace the current ad hoc system of appointing new judges for each dispute. I find mixed results, but one aspect that could speed up the process is that permanent judges develop established work relations and working methods
Keywords: F13; K41; 330; WTO; Dispute settlement; WTO panel; Trade disputes; Delays